2015
DOI: 10.1016/j.neuropsychologia.2014.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Language and task switching in the bilingual brain: Bilinguals are staying, not switching, experts

Abstract: Bilinguals’ ability to control which language they speak and to switch between languages may rely on neurocognitive mechanisms shared with non-linguistic task switching. However, recent studies also reveal some limitations on the extent control mechanisms are shared across domains, introducing the possibility that some control mechanisms are unique to language. We investigated this hypothesis by directly comparing the neural correlates of task switching and language switching. Nineteen Spanish-English bilingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 69 publications
(96 reference statements)
8
78
1
4
Order By: Relevance
“…Importantly, the involvement of the dlPFC and the ACC replicates previous studies relating language-switching in production to the left (Hernandez et al, 2000;Rodriguez-Fornells et al, 2005;Wang et al, 2007) and right (Hernandez et al, 2001;Wang et al, 2007) dlPFC, and in comprehension to the left ACC . The language switch effects localized in the dlPFC in production also extended to category-switching, consistent with previous studies (De Baene et al, 2015) and the hypothesis that language control is a subdomain of general cognitive control (Craik and Bialystok, 2006;Garbin et al, 2010;Abutalebi et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Importantly, the involvement of the dlPFC and the ACC replicates previous studies relating language-switching in production to the left (Hernandez et al, 2000;Rodriguez-Fornells et al, 2005;Wang et al, 2007) and right (Hernandez et al, 2001;Wang et al, 2007) dlPFC, and in comprehension to the left ACC . The language switch effects localized in the dlPFC in production also extended to category-switching, consistent with previous studies (De Baene et al, 2015) and the hypothesis that language control is a subdomain of general cognitive control (Craik and Bialystok, 2006;Garbin et al, 2010;Abutalebi et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Following previous studies that have found language-switching to recruit dorsolateral areas of the prefrontal cortex (dlPFC) in both hemispheres (Hernandez et al, 2000(Hernandez et al, , 2001RodriguezFornells et al, 2005;Wang et al, 2007), we analyzed Brodmann areas (BAs) 9, 10, and 46 bilaterally. Furthermore, because language-switching has been reported to involve the left ACC (Wang et al, 2007;Abutalebi et al, 2008, Crinion et al, 2006van Heuven et al, 2008), we also analyzed this area, including BA24, BA32, and BA33 in the analyses (MacDonald et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations